2016
DOI: 10.1002/aic.15190
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial tensions of industrial fluids from a molecular‐based square gradient theory

Abstract: This work reports a procedure for predicting the interfacial tension of pure fluids. It is based on scaling arguments applied to the influence parameter of the van der Waals theory of inhomogeneous fluids. The molecular model stems from the application of the Square Gradient Theory to the SAFT-VR Mie equation of state. The theory is validated against computer simulation results for homonuclear pearl-necklace linear chains made up to six Mie (λ − 6) beads with repulsive exponents spanning from λ = 8 to 44 by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 116 publications
2
65
0
1
Order By: Relevance
“…The SAFT-γ Mie force field and the corresponding equation of state have been incorporated through the use of a density gradient theory to predict the interfacial tensions of fluids analytically [20]. This method, despite being amongst the most accurate correlations available, is essentially based on an equation of state and not on actual molecular modelling; thus it was not deemed to fall within the remit of the challenge and is not discussed further.…”
Section: Generalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAFT-γ Mie force field and the corresponding equation of state have been incorporated through the use of a density gradient theory to predict the interfacial tensions of fluids analytically [20]. This method, despite being amongst the most accurate correlations available, is essentially based on an equation of state and not on actual molecular modelling; thus it was not deemed to fall within the remit of the challenge and is not discussed further.…”
Section: Generalitiesmentioning
confidence: 99%
“…Preliminary runs of the mixture system demonstrated that this was indeed the case and an appreciable adsorption of toluene at the interface was to be expected (see next section). We employed the SAFT equation of state coupled to square gradient theory [20] to obtain an estimate of this enhancement and to backtrace the required global compositions for these systems. A simplification may be made if one assumes that the organic composition in the aqueous phase is negligible.…”
Section: Molecular Simulation Detailsmentioning
confidence: 99%
“…Eine einfache Korrektur der CNT, etwa alleine durch Annahme einer größenabhängigen Oberflächenspannung, genügt daher nicht , . Vorhersagen sind in Verbindung mit der Dichtegradiententheorie , und der PC‐SAFT‐Zustandsgleichung , möglich, wenn der kinetische Beitrag zur Nukleationsrate an die Ergebnisse der vorliegenden MD‐Simulationen angepasst wird , . Aus dieser Verbindung von Dichtegradiententheorie, molekularer Zustandsgleichung und molekularer Simulation konnte in SkaSim eine hybride Nukleationstheorie als neuartiger theoretischer Ansatz entwickelt werden .…”
Section: Massiv‐parallele Molekulardynamik‐simulation Der Gasblasenbiunclassified
“…A number of papers dedicated to development the predicting methods for the surface tension of pure liquids and their mixtures [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] have been published from the middle of the last century to the presents. These methods can be divided into two types: empirical correlations and methods based on thermodynamic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…As can we see from short review, the major number of studies on predicting the surface tension considered pure liquids. There is some progress in predicting the surface tension of various mixtures using the thermodynamic approach [11,20,21]. There are some studies dedicated predicting the surface tension of mixtures refrigerants and solutions of refrigerant in compressor oil [5,7,22,23], that we are interested in.…”
Section: Introductionmentioning
confidence: 99%